The Shift of a Surau to Be a Mushalla as a Non-Formal Education Implementation in The Regency of West Sumatra Agam - Ahmad Sabri; Sermal Sermal; Syukra Vadhillah; Atqo Akmal; Sarah Pilbahri (Nazhruna: Jurnal Pendidikan Islam, 2022)
The concept of "surau" for the Minangkabau community cannot be separated from the framework of the Minangkabau Nature conception itself concerning the process of Islamization and its relationship to sociocultural (customary) aspects. Under ideal conditions, the surau used to function as a means of Islamic education, such as learning to recite the Qur'an, studying religious knowledge, or suluk (for the tarekat community), as well as as a means of inheriting certain traditions of the Minangkabau community such as learning to worship (petatah-petitih), art self-defense (silek), and qasidah/gambus. So, the concept of traditional surau education is a cultural heritage of the Minangkabau community in education, which is packaged in the form of non-formal education. However, over time the dynamics of the continuity of non-formal education based on the surau are affected by the modernization of education, social changes in society, and waves of religious reformism. This study found that surau-based non-formal education has experienced a shift in its educational function and model that occurs in three patterns: (1) Transformation, where the education governance has improved by transforming into formal educational institutions such as madrasas or pesantren, generally, this pattern occurs in a surau that has an excellent reputation.